PERDAMAIAN SEBAGAI PROSES RESOLUSI KONFLIK KELUARGA KRISTEN - Lourine Since Joseph (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2018)
Peace, tranquility, stability and happiness are the desires of human life, including Christian families. Consciously or not every individual in the life of a Christian family craves such a living situation. However, in fact, conflict is the reason for Christian families living in unhappiness, unease, unhappiness. Love and affection are lost due to the feeling and conviction that emerge as a way of life that is far from peaceful. Inner feelings and wounds outweigh the will of peace, stance exceeds the hope of living peacefully. Peace is one of the ways in the process of conflict resolution over conflicts that occur including Christian family conflicts. The way is through dialogue and communication with love and affection through conversation, dialogue with actions and attitudes, then the Christian family's peace is revealed.Key words: peace, family conflict